Expression and functional role of LncRNA GSEC in oral squamous cell carcinoma (Central Asian Journal of Medical Sciences, 2025)
Objective: The current investigation seeks to elucidate the regulatory impact of the long non-coding RNA GSEC (lncRNA GSEC) on oncogenic mechanisms in oral squamous cell carcinoma. Methods: The expression dynamics of GSEC were systematically mapped across in vitro systems, including healthy oral keratinocyte controls (NHOK) and their malignant counterparts (SCC-25, SCC-9, CAL-27), utilizing standardized qRT-PCR protocols. CAL-27 (highest GSEC expression) underwent siRNA-mediated knockdown. The assessment of cellular functions such as proliferation, apoptosis regulation, mobility, and invasion was conducted utilizing validated protocols: CCK-8 for cell viability assessment, flow cytometry for apoptotic cell identification, Transwell systems for measuring invasive ability, and scratch assay for migration analysis. mRNA and protein levels of proliferation/apoptosis markers (Ki67, PCNA, BCL-2, BAX, caspase-9) were analyzed by qRT-PCR, Western blot, and immunofluorescence. Results: GSEC was significantly upregulated in OSCC cells vs. NHOK (p